Students' Learning Interest In Following The Process Pjok Learning At Mi Miftahul Ulum Plinggisan - Millah, Achmad Sirojul; Kusmawati, Wiwik; Ali Muarifuddin, Moh; Sucpto, Adi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research uses quantitative descriptive methods to measure and analyxe The level of student interest in learning following the PJOK learning process at MI Miftahul Ulum Plinggisan. This method aims to get a clear picture of the factors that influence students' learning interest and the effectiveness of the strategies that have been implemented. The population of this study was all students at MI Miftahul Ulum Plinggisan, with samples selected randomly to ensure representation from each class. The research instrument is a questionnaire consisting of four main parts: Learning Motivation, Enjoyment, Involvement, and Perceptions of PJOK Lessons. Each section consists of several statements which are measured using a Likert scale with a range of 1 (Strongly Disagree) to 5 (Strongly Agree). Data collection was carried out by distributing questionnaires to students who were research samples, with filling in under the supervision of researchers to ensure completeness and accuracy of the data. The collected data was analyzed using descriptive statistical techniques, including editing and coding, tabulation, calculating descriptive statistics (mean, median, mode, and standard deviation), as well as Pearson correlation analysis to see the relationship between the variables motivation, enjoyment, involvement, and perception with interest. student learning. The research results showed that as many as 70% of students felt motivated to take part in PJOK lessons, as many as 80% of students enjoyed the activities in learning PJOK, as many as 80% of students were active in PJOK activities. As many as 75% of students have a positive view of the importance of PJOK lessons.